Secular variations of geomagnetic declination in the Karadag point and the global helio-geodynamic processes - Volvach, A. E.; Kurbasova, G. S. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2019)
To study the changes in the local variations of geomagnetic field, the Karadag point was chosen due to the fact that we found previously on increased insolation and the surface temperature of the earth at this point over the last century (compared to other Crimea points). For the analysis, the data calculated by the authors with a calculator of the 12th model of the International Geomagnetic Standard Field (The International Geomagnetic Reference Field — IGRF-12) were used. A polynomial model of the sixth order of secular variations of geomagnetic declination was constructed at the Karadag point for the period 1900—2017. The estimates of the accuracy of approximation by this model of the data calculated with the IGRF-12 calculator are as follows: R-square = 0.8892 (most of the variance is taken into account by the model); corrected R-square = 0.8833; mean square error of approximation RMSE = 0.01395. When comparing the graphs of secular variations of geomagnetic declination at the Karadag point calculated by means of the IGRF-12 calculator and using a polynomial order model, a leap in 1969 is detected. In addition, it was found that the most drastic changes in geomagnetic declination occurred at intervals of 1944—1945 and 1974—1975. Coherent variations are established. An analysis of the calculated coherence functions suggests the existence of a statistical connection between variations with a period of 36.4 years (the square of the coherence modulus is 62 %) in the secular variations of geomagnetic declination at Karadag and in changes from year to year of day duration; between variations with periods of 10.5 years (the square of the coherence modulus is 86 %) in the secular variations of geomagnetic declination at Karadag and changes in the number of sunspots from year to year. There is a similarity between the tendency of changes in the secular variations of geomagnetic declination at Karadag and the tendencies of changes in the northern component of the velocity of the geomagnetic pole in the Northern Hemisphere during recent years.